Screen-Printed Electrode Modified with Silver Hexacyanoferrate-Nafion® for Ascorbic Acid Determination - Zagal-Moya, J; Zagal-Moya, J; Segura-Segura, R; Segura-Segura, R (2011)
A flow injection system using a new and/or re-used graphite screen-printed electrode modified with silver hexacyanoferrate and a Nafion® polymer layer (AgHCF/GSPE) was employed for the determination of ascorbic acid in orange juice and drugs samples. Both modified electrodes showed an initial sensitivity of 0.015 A.cm-2.M-1, with a linear response over the range from 50 to 300 mg L-1 , relative standard deviations smaller than 2%, detection and quantification limits of c.a. 5.0 and 25.0 mg.L-1. The response of the electrodes was stable, with no variation of base line after 6-8 hours of continuous operation. With this system it is possible to measure 65-70 samples (20?L) per hour. By using 1.06 mg of AgNO3, 4.12 mg of K3Fe(CN) 6, 50.5 mg of KNO3 and 800?L of HNO3, it is possible to obtain between 25 and 30 modified electrodes. The proposed system showed to be inexpensive, versatile, robust and suitable for industrial application. The surface morphology of the bare and/or modified graphite screen-printed electrode was characterized by scanning electron microscopy.